2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin potential impacts on peripheral blood mononuclear cells of endometriosis women - Tanha, Mahsa; Bozorgmehr, Mahmood; Shokri, Mohammad-Reza; Edalatkhah, Haleh; Tanha, Mahya; Zarnani, Amir-Hassan; Nikoo, Shohreh (Elsevier Ireland Ltd, 2022)
Endometriosis happens following the implantation of endometrial-derived tissues outside the uterine cavity. It has been suggested that 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is involved in endometriosis development. Furthermore, aryl hydrocarbon receptor (AHR), as a TCDD receptor, has been demonstrated to regulate immune responses. Nonetheless, data regarding the mechanisms, through which TCDD influences the immune system in endometriosis, are still inconclusive. Therefore, frequency of regulatory T cells (Tregs) and the expression of FOXP3, AHR and indoleamine 2, 3-dioxygenase 1 (IDO1) from endometriosis and nonendometriosis individuals were investigated in the absence and presence of TCDD; also, the concentration of IL-6 and kynurenine in the supernatant of cultures was assessed. The impact of TCDD-treated PBMCs on the migration capacity of menstrual blood-derived stromal stem cells (MenSCs) and monocyte chemoattractant protein-1 (MCP-1) and IL-6 production was determined. Here, we found that AHR and IDO1 expression levels were lower in endometriosis PBMCs; however, TCDD treatment increased AHR, FOXP3, IDO1, IL-6, and Treg levels in the endometriosis group (P < 0.05-0.0001). TCDD-treated PBMCs increased the migration capacity of MenSCs and up-regulated MCP-1 and IL-6 levels in the PBMCs/MenSCs co-culture (P < 0.01-0.0001). In conclusion, these results shed light on the probable mechanisms, through which AHR activation by chemical toxicants can impact inflammatory immune mediators involved in the development of endometriosis; also, these data support the idea that TCDD could promote endometriosis progression.
Keywords: Endometriosis; Regulatory T cells (Tregs); Aryl hydrocarbon receptor (AHR); 2; 3; 7; 8-Tetrachlorodibenzo-p-dioxin (TCDD); Indoleamine 2; 3-dioxygenase 1 (IDO1)